Development and Evaluation of Laboratory Conditioning Procedures to Simulate Mixture Property Changes Effectively in the Field. Issue 1 (January 2014) - Isola, Marco; Chun, Sanghyun; Roque, Reynaldo; Zou, Jian; Koh, Chulseung; Lopp, George
The study reported here involved the development and evaluation of laboratory conditioning methods and testing protocols to consider heat oxidation and moisture that would simulate more effectively asphalt mixture aging in the field and thereby help to assess asphalt mixture property changes properly over time. In this study, "aging" was defined as any detrimental effect on asphalt mixture properties during the pavement life. Three laboratory conditioning procedures were identified and further developed to evaluate the effects of heat oxidation and moisture: heat oxidation conditioning (HOC), cyclic pore pressure conditioning (CPPC), and a combination of HOC and CPPC. Cores from aged field pavements were used in the energy ratio approach, which could integrate various factors that affected cracking performance, including key mixture properties and pavement structure, to evaluate the effectiveness of the conditioning procedures. HOC was accomplished with the Superpave ® long-term oven aging (LTOA) procedure, and CPPC was employed to induce moisture damage to the asphalt mixtures. Results indicated that asphalt mixtures subjected only to oxidative aging did not exhibit drops in mixture fracture energy (FE) comparable to the level observed in the field. The inclusion of CPPC was able to induce additional damage effectively through simulation of long-term moisture intrusion and repeated internal water pressure under traffic load. Further, the combination of LTOA followed by CPPC led to the most relevant changes in fracture properties with a level of reduction in FE consistent with field observation.